Pengaruh Digital Marketing, Customer Experience dan Customer Trust Terhadap Repurchase Intention Secara Online Produk Kosmetik Wardah - Cika Melia (Universitas Nusantara PGRI Kediri, 2023)
The aim of this research is to test and analyse the effect of Digital Marketing, Customer Experience and Customer Trust as partially and simultaneously towards repurchase intention in Wardah's website and to know the most dominant variable that affects repurchase intention. The approach that is being used in the research is quantitative analysis. Population that is being used are all women that have done online purchasing in Wardah's website. Data that were collected, used survey method by giving out questionnaire to women that bought from Wardah's website, routinely, through last year and were located at Jabodetabek. Questionnaires collected as many as 160 respondents, the data is then processed using multiple linear regression method. Results of data analysis performed with the help of SPSS tools. Based on the results of this analysis it is known that the variables digital marketing, customer experience, and customer trust simultaneously have a positive and significant effect on repurchase intention on the Wardah website. Partially, the digital marketing, customer experience, and customer trust variables have proven to have a positive and significant effect on repurchase intention on the Wardah website. Partially, the digital marketing, customer experience, and customer trust variables have proven to have a positive and significant effect on repurchase intention on the Wardah website. Then in the results of the analysis the variable Customer Experience is the most dominant variable.